The Failure of Mediation in Divorce Cases Handling at Gorontalo Religious Court - Ahmad Faisal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
This research analyses the failure of mediation in divorce cases at the Gorontalo Religious Court. This phenomenon is counterproductive to the efforts of the Supreme Court of the Republic of Indonesia to prevent the accumulation of cases and also to ignore religious recommendations for reconciliation when in conflict. This research is qualitative in nature with data collection using observation, interviews and documentation. The data was then analysed critically descriptively. The results showed that mediation failures continued to increase due to technical and non-technical reasons. Technically, the typology of divorce cases generally puts one of the parties (generally the wife) in a difficult position with an accumulation of long-standing disappointment and discomfort. This condition makes it difficult for mediators (both judge mediators and non-judge mediators) to carry out the mediation function. Non-technically, the support system in terms of time, place, process and totality of task implementation (especially for judge mediators) does not appear to be sufficiently supportive. The fact that all judge mediators have not all attended mediator training is another non-technical factor affecting mediation failure. Thus, the failure of divorce case mediation is not caused by a single factor but an accumulation of technical and non-technical factors that are intertwined at the same time. As long as there is no education, advocacy and correction of these two aspects, mediation failures in religious courts will continue to occur.